The solution to the equation is p = 1/3 and q = undefined
<h3>How to solve the equation?</h3>
The equation is given as:
p^2 - 2qp + 1/q = (p - 1/3)
The best way to solve the above equation is by the use of a graphing calculator i.e. graphically
However, it can be solved algebraically too (to some extent)
Recall that the equation is given as:
p^2 - 2qp + 1/q = (p - 1/3)
Split the equation
So, we have
p^2 - 2qp + 1/q = 0
p - 1/3 = 0
Solve for p in p - 1/3 = 0
p = 1/3
Substitute p = 1/3 in p^2 - 2qp + 1/q = 0
So, we have
(1/3)^2 - 2q(1/3) + 1/q = 0
This gives
1/9 - 2/3q + 1/q = 0
This gives
2/3q + 1/q = -1/9
Multiply though by q
So, we have
2/3q^2 + 1 = -1/9q
Multiply through by 9
6q^2 + 9 = -q
So, we have
6q^2 + q + 9 = 0
Using the graphing calculator, we have
q = undefined
Hence. the solution to the equation is p = 1/3 and q = undefined
Read more about equations at:
brainly.com/question/13763238
#SPJ1
Hmm I would say x=q
Hope this helps u <3
Answer:
Step-by-step explanation:
Answer:
The correct option is 1/4^2
Step-by-step explanation:
The given expression is:
4^6 * 4^-8
According to the same base rule if the exponents have the same base then the exponents will be added.
If we look at the given expression both the values have the same base.
Therefore we will add the exponents of the value.
= 4^6+(-8)
= 4^6-8
= 4^-2
Now to change the negative exponent into positive we will take it to the denominator.
4^-2 = 1/4^2
Thus the correct option is A....